Intellectual analysis of case-based data in time series prediction - N.O. Rakhimov; D.E. Khojamberdiyev; H. Kamarov (International Journal on Human-Computing Studies, 2021)
The data analysis method is used to predict time series. This article discusses the method of intellectual analysis of precedent data, algorithm ideas and provides a diagram of the developed software